Current and emerging treatment options for hairy cell leukemia - López-Rubio, Montserrat (Onco Targets Ther, 2015)
Hairy cell leukemia (HCL) is a lymphoproliferative B-cell disorder characterized by pancytopenia, splenomegaly, and characteristic cytoplasmic hairy projections. Precise diagnosis is essential in order to differentiate classic forms from HCL variants, such as the HCL-variant and VH4-34 molecular variant, which are more resistant to available treatments. The current standard of care is treatment with purine analogs (PAs), such as cladribine or pentostatin, which provide a high rate of long-lasting clinical remissions. Nevertheless, ~30%–40% of the patients relapse, and moreover, some of these are difficult-to-treat refractory cases. The use of the monoclonal antibody rituximab in combination with PA appears to produce even higher responses, and it is often employed to minimize or eliminate residual disease. Currently, research in the field of HCL is focused on identifying novel therapeutic targets and potential agents that are safe and can universally cure the disease. The discovery of the BRAF mutation and progress in understanding the biology of the disease has enabled the scientific community to explore new therapeutic targets. Ongoing clinical trials are assessing various treatment strategies such as the combination of PA and anti-CD20 monoclonal antibodies, recombinant immunotoxins targeting CD22, BRAF inhibitors, and B-cell receptor signal inhibitors.